Marketing golden triangle for new era (OCB through HRE in AOP) - Nezakati, Hossein *; Asgari, Omid (2009)
This research attempts to propose a concept in Marketing New Era to present an approach (Golden Triangle) for achieving Organizational Citizenship Behavior (OCB) through Human Resource Empowerment (HRE) in Age of Par%cipa%on (AOP). The 9 stage Procedure for building this conceptual model is considered as: 1) prepara%on of individuals and management; 2) requirements for empowerment process and utilization of three international aspect of empowerment : National, Culture, Values; 3) three dimensions of HRE process and their symbolic aspects; 4) HRE emergence; 5) OCB dimensions in their innate forms and their enforcement during these procedures; 6) instrumental factors in crea%ng OCB and outcome of HRE in one procedure; 7) OCB symbolism and reach the point of Marke%ng 3.0; and 8) consequences of OCB and use them for age of par%cipa%on. 9) Finally reach to age of participation. The results of this study showed that eight factors out of eleven (73 percents of factors) that make up OCB and consequences of HRE are analogous indicating the fundamental relationship of HRE with OCB